FRI0487 APREMILAST IN MONOTHERAPY OR COMBINED IN NON-ULCER MANIFESTATIONS OF BEHÇET'S DISEASE. NATIONAL MULTICENTER STUDY OF 34 REFRACTORY CASES OF CLINICAL PRACTICE. (2nd June 2020) - Herrero Morant, A.; Atienza Mateo, B.; Loricera, J.; Calvo del Rio, V.; Martín-Varillas, J. L.; Espinosa, G.; Graña, J.; Moriano, C.; Pérez Sandoval, T.; Martín Martínez, M.; Diez, E.; García-Armario, M. D.; et al.
Abstract : Background: Apremilast (APR) has demonstrated efficacy in orogenital ulcers of Behçet´s disease (BD). Response of other clinical manifestations remains unknown. Objectives: To assess the efficacy and safety of APR in monotherapy or combined with disease-modifying anti-rheumatic drugs (DMARDs) in non-aphthous ulcers of BD. Methods: National multicenter open-label study on 34 BD patients treated with APR at maintained standard dose of 30 mg twice daily. Results: From a cohort of 51 patients with APR by refractory orogenital ulcers of BD, we selected 34 (24 women/10 men, mean age 43.8±14.3 years), cases with another clinical manifestation/s. Excluding CTs, colchicine or NSAIDs, APR was given in monotherapy (n=21) or combined with conventional and/or biologic DMARDs in 13 cases (5 methotrexate, 3 azathioprine, 3 hydroxychloroquine, 1 sulfasalazine, 1 dapsone, 2 tocilizumab, 1 IFX). Other active manifestations present at APR onset were: arthralgia/arthritis (16, true arthritis in 5), folliculitis/pseudofolliculitis (14), erythema nodosum (3), furunculosis (2), paradoxical psoriasis by TNFi (2), intestinal ileitis (2), deep venous thrombosis (2), leg ulcers (1), erythematosus and scaly skin lesions (1), fever (1), unilateral anterior uveitis (1) and neurobehçet (1). After a median follow-up of 6 [3-12] months, folliculitis and ileitis improved, neurobehçet remained stable and musculoskeletal manifestations evolved in a variable way. (TABLE) Conclusion: In addition of orogenital ulcers, APR in monotherapy or combined, seems to be useful in skin manifestations of BD Disclosure of Interests: Alba Herrero Morant: None declared, Belen Atienza Mateo: None declared, J. Loricera: None declared, Vanesa Calvo del Rio Grant/research support from: MSD and Roche, Speakers bureau: Abbott, Lilly, Celgene, Grünenthal, UCB Pharma, José Luis Martín-Varillas Grant/research support from: AbbVie, Pfizer, Janssen and Celgene, Speakers bureau: Pfizer and Lilly, Gerard Espinosa: None declared, Jenaro Graña: None declared, Clara Moriano: None declared, Trinidad Pérez Sandoval: None declared, Manuel Martín Martínez: None declared, Elvira Diez: None declared, María Dolores García-Armario: None declared, Esperanza Martínez: None declared, Ivan Castellví Consultant of: Boehringer Ingelheim, Actelion, Kern Pharma, Speakers bureau: Boehringer Ingelheim, Actelion, Bristol-Myers Squibb, Roche, Patricia Moya Alvarado: None declared, Francisca Sivera: None declared, Jaime Calvo Grant/research support from: Lilly, UCB, Consultant of: Abbvie, Jansen, Celgene, Isabel de la Morena: None declared, Francisco Ortiz Sanjuán: None declared, José Andrés Román Ivorra: None declared, Ana Pérez Gómez: None declared, Alejandro Olive: None declared, Carolina Díez: None declared, Juan José Alegre: None declared, D Ybáñez-García Speakers bureau: Lilly, Roche, Sanofi, Ángels Martínez-Ferrer: None declared, Javier Narvaez: None declared, Ignasi Figueras: None declared, Ana Isabel Turrión: None declared, Susana Romero-Yuste: None declared, Pilar Trénor: None declared, Soledad Ojeda Speakers bureau: AMGEN, LILLY, GEBRO, Miguel Á. González-Gay Grant/research support from: AbbVie, MSD and Roche, Speakers bureau: AbbVie, MSD and Roche, Ricardo Blanco Grant/research support from: Abbvie, MSD and Roche, Consultant of: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen and MSD, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Lilly and MSD